TINGKAT KEPUASAN WARGA TERHADAP KOMUNIKASI PARTISIPATIF PADA BENGKULU REGIONAL DEVELOPMENT PROJECT: KASUS DI DESA PONDOK KUBANG KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Mulyasari, Gita (Jurnal AGRISEP, 2011)
The successful of Bengkulu Regional Development Project was very determined by the society’s participation in all of the project activities. This research aimed to analyse satisfaction level felt by the society as the effect of participative communication in BRDP activities.   The research was conducted in Village of Pondok Kubang Sub District of Pondok Kelapa District of Central Bengkulu. Sampling was conducted by Simple Random Sampling, number of respondents that would be collected as many as 25 respondents.  The result showed satisfaction level that significant to the participative communication in BRDP activities. Keywords: satisafction level, partisipave communication, BRDP